The monetary and financial system - Goacher, David J.; Institute of Financial Services (Great Britain) (Canterbury : CIB Publishing, 2003)
Helps understand the role and functions of major financial institutions and markets. The revisions to this text expand upon the nature and functions of the major cash and derivative market financial instruments; the domestic and international regulatory environment in which financial institutions operate; the implications for th financial services industry of monetary policy and the major economic and other factors influencing the determination of interest rates and exchange rates.
Includes index.
At top of t.p.: "Institute of Financial Services.".
oif 21/07/14
Loan
Keywords: Finance; International finance; Money market